Agri-Food System Governance in Bangladesh’s Coastal Regions: Why the Socio-Ecological Systems Approach Needs to Be Politicized - Joshi, Deepa; Schulze, Paul; Amin, Md Nurul; Gallant, Bryce; Aheeyar, Mohamed M. M.; Rahman, Mokhlesur; Garrett, James; Sarker, Mou Rani (TU Delft, 2025)
While Bangladesh is reported as doing well in food production, there is increasing concern that this essentially deltaic and highly climate-vulnerable country will face steep challenges in food governance and productivity. Anthropogenic drivers shaped by narrow economic goals and sectoral policies have deeply altered Bangladesh’s food systems since the early 1960s and partly led to adverse outcomes. By combining policy and institutional analysis and primary research in Shyamnagar Upazila in Satkhira District in the southern coastal deltas, we revisit two key transi- tions – poldering and commercial shrimp farming – to reveal how diverse economic, social and political factors have shaped the effi ciency, inclusivity and sustainability of agri-food systems. These complex interactions between agri-food systems, the broader ecology and heterogeneity in poverty, gender and other social identities are poorly understood and accounted for in policies and programme interventions. This has resulted in unequal confl icts and contestations around critical resources, which impact most marginalized groups, also because policy incoherence encourages collusion between local elites and local decision-makers for resource appropriation and control. Conceptually, a social-ecological systems (SES) framework would identify these complexities. However, SES approaches tend to be technocratic and overlook the overtly economic framing of natural resources governance, diversity among local communities, and the politics of resource ap- propriation. This gap can be remedied by merging SES thinking with a critical political ecology lens to trace the historical, scalar and deeply intersectional nature of socio-ecological relations.